Production and Quality of Etawa Raw Milk Using Palm Oil Industry Waste and Paitan Plants as an Early Feed - Arief,; Elihasridas,; Somen, Simel; Roza, Elly; Pazla, Roni; Rizqan, (Pakistan Journal of Nutrition, 2018)
Objective: The aim of this research was to determine the influence of palm oil industry by-products (palm kernel cake and palm oil sludge) and Paitan (Tithonia diversifolia, TD) as roughage on the production and quality of Etawa crossbreed (EC) goat milk. Materials and Methods: Eighteen EC dairy goats on their second lactation month were used in this study. This study utilized a Completely Randomized Design (CRD) that consisted of 6 treatments and 3 replicates. The treatments were as follows: (A) 50% roughage+50% soybean meal waste (SMW)+0% palm oil concentrate (POC), (B) 50% TD+50% SMW+0% POC, (C) 50% TD+37.5% SMW+12.5% POC, (D) 50% TD+25% SMW+25% POC, (E) 50% TD+12.5% SMW+37.5% POC and (F) 50% TD+0% SMW+50% POC. The variables observed in this study were the production and quality of Etawa crossbreed milk (protein and lactose). Results: Results showed a milk production rate (1.44-1.85 kg/head/day) with a milk protein concentration (3.48-3.76%) and a lactose concentration (4.01- 4.16%). Using palm oil industry by-products and TD as an early feed can significantly increase milk production (p